Barriers to Global Health Training in Obstetrics and Gynecology - Rachel Pope; Maria Shaker; Prakash Ganesh; Margaret Larkins-Pettigrew; Stephanie Deter Pickett (Annals of Global Health, 2016)
Background The Lancet Commission on Global Surgery includes obstetrics and gynecology as an area needing international strengthening in low- and middle-income countries. Despite interest, a majority of participants in US residency programs graduate with little exposure to global health or preparation to work abroad. Objective The aim of this study was to determine the level of interest of obstetrics and gynecology (Ob/Gyn) residents in gaining global health training and to identify perceived barriers to receiving training. Methods Residents in accredited Ob/Gyn programs were identified using a national residency database. The survey was online and anonymous. Findings A total of 278 residents completed the survey. A high level of motivation to participate in a global health elective was associated with interests in preparation for future global work, desire for activism in maternal health and social determinants of health, and becoming better informed on global health policy. Eighty-two percent of respondents stated they would participate in a global health curriculum if it were offered, and 54.8% would use their vacation time. There were associations between personal safety, family, lack of resources, and lack of interest from faculty and motivational level as perceived barriers. Eighty-one percent strongly agreed that scheduling conflicts and time constraints pose barriers; more than 80% either agreed or strongly agreed that funding such endeavors and a lack of mentorship are major deterrents to pursuing global health. Conclusions Because resident motivation is clearly high and international need persists, we determined that most barriers to training abroad are related to the structure and budget of residency programs.